Vectorizing the spatial structure of high-harmonic radiation from gas - Kong, F. (Nat Commun, 2019)
Strong field laser physics has primarily been concerned with controlling beams in time while keeping their spatial profiles invariant. In the case of high harmonic generation, the harmonic beam is the result of the coherent superposition of atomic dipole emissions. Therefore, fundamental beams can be tailored in space, and their spatial characteristics will be imparted onto the harmonics. Here we produce high harmonics using a space-varying polarized fundamental laser beam, which we refer to as a vector beam. By exploiting the natural evolution of a vector beam as it propagates, we convert the fundamental beam into high harmonic radiation at its focus where the polarization is primarily linear. This evolution results in circularly polarized high harmonics in the far field. Such beams will be important for ultrafast probing of magnetic materials.